Comparison of Warming Needle Moxibustion and Drug Therapy for Treating Knee Osteoarthritis: A Systematic Review and Meta-analysis. (27th July 2022) - Li, Juan; Yang, Haizhou; Hu, Tianyan
Abstract : Objective. To compare the efficacy of warming needle moxibustion (WNM) with that of drug therapy for treating knee osteoarthritis (KOA), so as to provide evidence-based reference for the treatment of knee osteoarthritis. Methods. PubMed, Embase, Cochrane Library, VIP, WanFang, and CNKI were searched from inception to March 23, 2022. Literature selection was processed in strict accordance with inclusion and exclusion criteria. Cochrane Risk of Bias Assessment tool was applied for quality assessment of included studies. Data analysis and publication bias assessment were performed using Stata 15.0. Results. There were 30 RCTs included, with 1324 participants in the WNM group and 1293 in the control group. Meta-analysis showed that the WNM group yielded more excellent effect than the control group (R R = 1.22, 95% CI (1.17, 1.27), p = 0 ), improvement in WOMAC scores was greater in the WNM group than in the control group (WMD = − 8.48, 95% CI (-13.13, -3.83), p = 0.002 ), activity of daily living (ADL) score was higher in the WNM group than in the control group (WMD = − 7.66, 95% CI (-10.22, -5.09), p = 0.01 ), improvement in joint stiffness scores was greater in the WNM group than in the control group (WMD = -1.72, 95% CI (-2.50, -0.93), p = 0.005 ), and improvement in pain scores was greater in the WNM group than in the control group (SMD = − 1.09, 95% CI (-1.38, -0.79), p = 0.001 ). Conclusions. WNM would be more effective in improving quality of life, decreasing WOMAC score, promoting knee function recovery, and alleviating the joint pain and stiffness, compared with orally taken drug therapies. Therefore, WNM could be given prior consideration for the treatment of KOA.